REVITALIZATION OF LOCAL TRADITIONS AS A MEDIUM FOR CHILDREN'S CHARACTER EDUCATION IN INDIGENOUS COMMUNITIES - Ridho, Ali; Arifin, Samsul; Dannur, Moh; Rahmawati, Roro Kurnia Nofita (Ngejha, 2025)
This study aims to analyze the role of local traditions as a medium for children's character education in indigenous communities and formulate effective revitalization strategies during globalization challenges. With an ethnographic qualitative approach, the research was conducted through participatory observation, in-depth interviews with indigenous stakeholders, parents, and children, and analysis of related documents in various indigenous communities in Indonesia. The results of the study revealed that local traditions such as rituals, folklore, and traditional games contain important character values such as honesty, cooperation, and respect for nature. However, its effectiveness as an educational medium faces challenges due to global cultural penetration and a lack of institutional support. The study's key findings suggest that revitalizing local traditions requires an adaptive approach that blends traditional wisdom with contemporary innovation. Communities that successfully maintain the relevance of traditions generally develop strategies such as integration with formal education, the use of digital media, and intergenerational approaches in knowledge transmission. The study also identified three factors that determine success: (1) the active involvement of the young generation in the revitalization process, (2) adequate policy support, and (3) flexibility in traditional methods of conveying values. The results of this study make an important contribution to the development of a character education model based on local wisdom that remains relevant in the modern era, while offering a conceptual framework to combine cultural preservation with contemporary educational needs.